First characterization of Pompia intrea candied fruit: The headspace chemical profile, polar extract composition and its biological activities. (June 2019) - Deiana, Monica; Montoro, Paola; Jerković, Igor; Atzeri, Angela; Marijanović, Zvonimir; Serreli, Gabriele; Piacente, Sonia; Tuberoso, Carlo Ignazio Giovanni
Abstract: Extracts obtained from Pompia intrea (PI), a traditional candied fruit whose main ingredient is the pompia fruit ( Citrus monstruosa L.) were evaluated for the first time. Volatile compounds were evaluated by headspace solid-phase microextraction (HS-SPME) followed by GC-FID/MS analyses. Polar compounds were identified by high-performance liquid chromatography coupled with electrospray mass spectrometry LC-ESI-Orbitrap-MS/MS and quantified by liquid chromatography coupled with ultraviolet/visible detection (LC-DAD). The antioxidant activity of these extracts was tested using the FRAP, CUPRAC, ABTS + and DPPH ● assays. Moreover, their ability to protect intestinal cells against lipid peroxidation was studied. The HS-SPME GC-FID/MS confirmed the presence of typical molecules originating from the fruit (mainly terpenes, but particularly limonene). The LC-DAD and LC-ESI-(HR)MS n profiles showed high levels of neohesperidin (45.7 ± 11.1 mg/L) and 5-(hydroxymethyl)furfural (40.8 ± 23.5 mg/L). The results showed that the PI extracts contained high levels of total phenols and exhibited considerable antioxidant activity, which was significantly correlated to the presence of specific compounds such as neoeriocitrin and neohesperidin. Furthermore, pretreatments with different concentrations of PI extracts preserved enterocytes from oxidative damage by scavenging reactive oxygen species, thus counteracting lipid peroxidation. This study suggests that consumption of PI could provide intake of compounds with ascertained biological activity. Graphical abstract: Unlabelled Image Highlights: Extracts obtained from Pompia intrea candied fruits were evaluated. A comprehensive study on the antioxidant activities was performed. Limonene was the most representative volatile compound. LC-ESI-(HR)MS/MS and LC-DAD showed a high amount of flavanones. Phenolic extracts showed relevant antioxidant properties in Caco-2 cells monolayers.